2018
DOI: 10.3390/pharmaceutics10030124
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tissue Distribution and Excretion of a Novel Diuretic (PU-48) in Rats

Abstract: Methyl 3-amino-6-methoxythieno [2,3-b] quinoline-2-carboxylate (PU-48) is a novel diuretic urea transporter inhibitor. The aim of this study is to investigate the profile of plasma pharmacokinetics, tissue distribution, and excretion by oral dosing of PU-48 in rats. Concentrations of PU-48 within biological samples are determined using a validated high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. After oral administration of PU-48 (3, 6, and 12 mg/kg, respectively) in self-nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Actually, there have been certain UT inhibitors (e.g. PU-14, PU-48, PU1424, CB-20, and 8n) discovered and developed to inhibit all UTs (42)(43)(44)(45)(46)(47). In this case, however, side effects can not be ignored because that UT-B-KO mouse was found to exhibit depression-like behavior (48) and to induce DNA damage and apoptosis in bladder (49), which attributed to elevated level of urea.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there have been certain UT inhibitors (e.g. PU-14, PU-48, PU1424, CB-20, and 8n) discovered and developed to inhibit all UTs (42)(43)(44)(45)(46)(47). In this case, however, side effects can not be ignored because that UT-B-KO mouse was found to exhibit depression-like behavior (48) and to induce DNA damage and apoptosis in bladder (49), which attributed to elevated level of urea.…”
Section: Discussionmentioning
confidence: 99%
“…Further optimization of PU-48 yielded a thienopyridine UT inhibitor ( Fig. 1 D) with improved water solubility and activity almost equal to that of PU-48 in vitro and in vivo 32 , 37 , 39 , 40 . Dimethylthiourea, an urea analogue with millimolar potency for UT inhibition was identified in previous studies ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported reduced blood pressure and essentially no physiological abnormalities in the extrarenal organs. Indeed, this specific disorder in the ability of the kidney to concentrate urine in UTs knockout mice supports the rationale behind the development of UT inhibitors as novel diuretics (Esteva-Font et al, 2013;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 66%